Design and Performance Analysis of a Composite Separator with Enhanced De-Bonding Efficiency of Gas Hydrate-Bearing Sediments - Xing Fang; Yufa He; Zhong Li; Guorong Wang; Shunzuo Qiu (Applied Sciences)
In the marine natural gas hydrate solid-fluidization mining process, current separation devices are insufficient in de-bonding the hydrate cementation between sand particles, affecting the hydrate collection efficiency. To address this issue, a composite separator was designed in this study that is used to restrict the axial movement of cemented particles, thereby achieving the goal of enhanced de-bonding efficiency. A combined computational fluid dynamics–discrete element method simulation method was used to verify the de-bonding performance of this composite separator on weakly cemented hydrate particles with different sizes and to study the influence of the spiral flow channel structural parameters and inlet types on the de-bonding performance.